ROLE OF THE GREEN ECONOMY IN SUSTAINABLE DEVELOPMENT - Rani, Puspa; Sharma, Shiromani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Effects that are Beneficial to the Natural World The green economy has the potential to play a number of vital functions, with the accomplishment of environmental sustainability and the development of solutions to major environmental challenges being two of the most important roles that it may potentially play. All of these tasks, as well as others, are within the scope of possibility for an economy that prioritizes environmental sustainability. This is made possible by the organization placing a significant emphasis on environmentally responsible business practices, renewable energy sources, and the effective use of available resources. As a direct consequence of this, there are a great many advantageous effects on the surrounding environment. These advantages can be seen all around. There is a connection between having a sustainable economy and reducing the amount of greenhouse gasses that are released into the atmosphere. The subsequent sentence provides further evidence of this link. One of the key goals of the transition to renewable energy sources and other energy efficiency measures is to reduce reliance on fossil fuels, which are among the most significant contributors to climate change. Other energy saving techniques also aim to improve overall energy efficiency. This target is one of the primary goals that must be accomplished during the transition.